Pengaruh Model Pembelajaran Time Token terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII di SMP Qur’aniah 1 Palembang - Hesti Rahayu; Dina Sri Nindiati (LP4MK STKIP PGRI Lubuklinggau, 2021)
Currently, many teachers have implemented various learning models so that students do not feel bored when the learning process takes place. One of them is the Time Token learning model. Time Token is taken from the word Time which means time and Token which means sign, where each student gets the opportunity to give their opinion in turn until the talking card runs out. In social studies learning itself, this learning model is applied so that students speak actively and avoid students dominating the conversation or being completely silent. The purpose of this study was to determine the effect of the application of the Time Token learning model on student learning outcomes in social studies class VIII at SMP Qur'aniah 1 Palembang. The method used is the quantitative / experimental method. Data collection techniques used documentation techniques and tests. The results showed that tcount = 9.038> ttable = 1.671., Then Ho was rejected and Ha was accepted, and it was seen from the increase in the average value of the experimental class from 74 to 81, and if the percentage calculation increased by 9%. Which means that it can be concluded that there is an effect of the application of the Time Token learning model on student learning outcomes in IPS class VIII subjects at SMP Qur'aniah 1 Palembang.